Involvement of Fenton Reaction on Biodecolorization and Biodegradation of Methylene Blue Dye by Brown Rot Fungi Daedalea dickinsii - Adi Setyo Purnomo; Alya Awinatul Rohmah; Weni Sri Ekowati; Hamdan Dwi Rizqi; Asranudin Asranudin (Universitas Gadjah Mada, 2023)
The disposal of dye wastewater has become a major global concern. Meanwhile, microorganisms have shown high potential in the treatment of wastewater pollutants. In this study, the involvement of the Fenton reaction in the biodecolorization and biodegradation of methylene blue (MB) by the brown rot fungus Daedalea dickinsii was investigated. Subsequently, D. dickinsii is a fungus capable of producing hydroxyl radicals (•OH). This experiment was conducted with an initial MB concentration of 75 mg/L, and different incubation times of 0, 7, 14, 21, and 28 d respectively. The result showed that the Fenton reaction played an important role, and this was demonstrated by the addition of FeSO4 as a Fe2+ source. The removal of MB by D. dickinsii with the addition of Fe2+ reached 91.454% at 28 d in a mineral salt medium. It was higher compared to D. dickinsii culture treatment without Fe2+ addition, 86.427%. Furthermore, the metabolic degradation product was analyzed using LC-TOF/MS and identified as 2-amino-3-hydroxy-5-(methylamino) benzenesulfonic acid and N-(3,4-dihydroxy phenyl)-N-methyl formamide.